Bài 1:Làm tính nhân a) (4xy^3+2x^2y^-x^2y).(-3x3y) b) (2x^2-3).(x+3x^2-4) 27/07/2021 Bởi aihong Bài 1:Làm tính nhân a) (4xy^3+2x^2y^-x^2y).(-3x3y) b) (2x^2-3).(x+3x^2-4)
Đáp án: Giải thích các bước giải: `a) (4xy^3+2x^2y^2-x^2y).(-3x^3y)` `=-12x^4y^4-6x^5y^3+3x^5y^2` `b) (2x^2-3).(x+3x^2-4)` `=2x^3+6x^4-8x^2-3x-9x^2+12` `=6x^4+2x^3-17x^2-3x+12` Bình luận
Đáp án: a/ $-12x^4y^4-6x^5y^3+3x^5y^2$ b/ $6x^4+2x^3-17x^2-3x+12$ Giải thích các bước giải: a/ $(4xy^3+2x^2y^2-x^2y).(-3x^3y)$ $=4xy^3.(-3x^3y)+2x^2y^2.(-3x^3y)-x^2y.(-3x^3y)$ $=-12x^4y^4-6x^5y^3+3x^5y^2$ b/ $(2x^2-3).(x+3x^2-4)$ $=2x^2.(x+3x^2-4)-3(x+3x^2-4)$ $=2x^3+6x^4-8x^2-3x-9x^2+12$ $=6x^4+2x^3-17x^2-3x+12$ Chúc bạn học tốt !!! Bình luận
Đáp án:
Giải thích các bước giải:
`a) (4xy^3+2x^2y^2-x^2y).(-3x^3y)`
`=-12x^4y^4-6x^5y^3+3x^5y^2`
`b) (2x^2-3).(x+3x^2-4)`
`=2x^3+6x^4-8x^2-3x-9x^2+12`
`=6x^4+2x^3-17x^2-3x+12`
Đáp án:
a/ $-12x^4y^4-6x^5y^3+3x^5y^2$
b/ $6x^4+2x^3-17x^2-3x+12$
Giải thích các bước giải:
a/ $(4xy^3+2x^2y^2-x^2y).(-3x^3y)$
$=4xy^3.(-3x^3y)+2x^2y^2.(-3x^3y)-x^2y.(-3x^3y)$
$=-12x^4y^4-6x^5y^3+3x^5y^2$
b/ $(2x^2-3).(x+3x^2-4)$
$=2x^2.(x+3x^2-4)-3(x+3x^2-4)$
$=2x^3+6x^4-8x^2-3x-9x^2+12$
$=6x^4+2x^3-17x^2-3x+12$
Chúc bạn học tốt !!!